The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/ijc.2910620513
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and cervical neoplasia: A case‐control study in Taiwan

Abstract: Multiple sexual partners and early age at first intercourse have been identified as major risk factors for cervical cancer in earlier epidemiologic studies (Brinton, 1992), implying that sexually transmitted agents might be involved in its etiology. Over the last decade, mounting evidence from laboratory (zur Hausen, 1994) and epidemiologic (Muiioz et al., 1992; Peng et aZ., 1991) studies has shown that sexually transmitted infection with genital types of human papillomavirus (HPV) may be the primary causal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
55
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 19 publications
13
55
2
Order By: Relevance
“…1,2 The unusually high prevalence of HPV 52 and 58 has been reported in Chinese populations living in China 3,4 and Taiwan. [5][6][7][8] In a previous report of our study, the prevalence of high-grade squamous intraepithelial lesion (HSIL) or worse lesions among participants with single-type infection of HPV 16, HPV 58 and HPV 52 at study entry was 31.9, 35.7 and 13.3%, respectively. 9 The participants infected with HPV 16, HPV 58 or HPV 52 had an increased prevalence of cervical cancer and carcinoma in situ (CIS).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…1,2 The unusually high prevalence of HPV 52 and 58 has been reported in Chinese populations living in China 3,4 and Taiwan. [5][6][7][8] In a previous report of our study, the prevalence of high-grade squamous intraepithelial lesion (HSIL) or worse lesions among participants with single-type infection of HPV 16, HPV 58 and HPV 52 at study entry was 31.9, 35.7 and 13.3%, respectively. 9 The participants infected with HPV 16, HPV 58 or HPV 52 had an increased prevalence of cervical cancer and carcinoma in situ (CIS).…”
mentioning
confidence: 53%
“…In several previous studies, the high prevalence of HPV 52 and HPV 58 has been reported in Chinese populations. [3][4][5]7,8,29 Our study was the first comprehensive study on the genetic variations of E6-E7-LCR of HPV 52 and 58 and their association with cervical neoplasia in Taiwan.…”
Section: Discussionmentioning
confidence: 88%
“…[8][9][10][11][12][13][14][15]36,37 The overall presence of HPV 16, 18, 52, 58, 31 and 33 E6 mRNA transcripts (68.7%) in the 6 types of HPV DNA-positive cases in CIN lesions is higher than that in a previous study (46%). 21 The presence of these 6 types mRNA transcripts with HPV DNA positive is 80% for CIN 3 but only 13% for normal cytology.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, HPV 52 and 58 are more prevalent in patients with preinvasive and cervical cancer in Taiwan and other Asian countries. [8][9][10][11][12][13][14][15] On the other hand, the occurrence of infection with HPV types 52 or 58 is relatively uncommon in cervical cancer in the Americas, Europe, Africa and …”
mentioning
confidence: 99%
“…This was synthesized with multiple nucleotides in each primer and mixed with 25 primers including HMB01M, which detect a large spectrum of HPV types? This has been used in North and South America as well as in Asia (Wheeler et al, 1993;Hildesheim et al, 1994;Ley et al, 1994;Liaw et al, 1995;Lazcano et al, 2001;Thomas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%